Kualitas Pelayanan Administrasi Kependudukan Melalui Website “Plavon” Dukcapil di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sidoarjo - Rayhan Surya Putra; Tukiman (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Public services in Indonesia are one of the strategic issues because the impact is very broad and touches all public spaces. However, the quality or quality that is improved tends to run in place. The implementation of e-government is expected to be able to advocate between the demands of the community in obtaining appropriate, effective and efficient services from the city government, by utilizing Information and Communication Technology (ICT). With the use of ICT, the Population and Civil Registration Office of Sidoarjo Regency made a breakthrough in Online Service innovation or commonly referred to as Plavon Dukcapil. The purpose of this study is to determine the Quality of Population Administration Services through the Plavon Dukcapil Website at the Population and Civil Registration Office of Sidoarjo Regency. The method used in this study is descriptive qualitative. This research will focus on service quality indicators located in 5 dimensions said by Parasuraman, Zeithaml, &; Berry (in Hardiyansyah, 2011: 11), namely; Tangibles, Reliability, Responsiveness, Assurance, and Emphaty. Data collection techniques used in this study are interviews with informants, direct observation in the field, and documentation. In its implementation, Plavon Dukcapil can be said to be of poor quality because there are problems that exist in the lack of human resources in completing applications for population documents so that the document completion time tends to be long, there is no filter for service bureaus, and lack of socialization from the government about Plavon Dukcapil.